Anaplasma spp. infection in smallholder goat flocks around Gaborone, Botswana - Berthelsson, Jessica (SLU/Dept. of Clinical Sciences (until 231231), 2017)
Anaplasma is a genus of gram-negative, intracellular bacteria infecting different blood cells in animals. Three of the species infect the erythrocytes of ruminants, A. marginale and A. centrale most often infect cattle, while A. ovis primarily infects sheep and goats. Different species of wild ruminants can also become infected. The disease is called anaplasmosis and causes clinical signs like hemolytic anaemia, icterus and loss of production. In this study samples were collected from smallholder goat flocks around Gaborone in Botswana. Blood samples were collected from 100 goats in 11 different flocks from three different villages; Modipane, Kopong and Gakuto. Body condition and FAMACHA© scores were estimated and the blood was used for PCV, blood smears, cELISA and PCR. Each farmer was interviewed about management, health and treatment of the goats. Examination of blood smears in light microscopy showed inclusion bodies in 53% of the samples. A seroprevalence of 88% was found on cELISA and 76% of the goats were positive on PCR with a general primer for Anaplasma spp. The PCR positive samples were used for specific PCR for detecting A. marginale and A. ovis. All the PCR positive goats were infected with A. ovis and no goats were positive for A. marginale. Positive animals were found in all areas and in all flocks. The prevalence was highest in Modipane and lowest in Gakuto.